Spatial modulation spectroscopy for imaging and quantitative analysis of single dye-doped organic nanoparticles inside cells. Issue 21 (12th May 2015) - Devadas, Mary Sajini; Devkota, Tuphan; Guha, Samit; Shaw, Scott K.; Smith, Bradley D.; Hartland, Gregory V.
Abstract : The loading and distribution of non-fluorescent dye-doped lipid-polymer nanoparticles in cells has been investigated by spatial modulation spectroscopy. Abstract : Imaging of non-fluorescent nanoparticles in complex biological environments, such as the cell cytosol, is a challenging problem. For metal nanoparticles, Rayleigh scattering methods can be used, but for organic nanoparticles, such as dye-doped polymer beads or lipid nanoparticles, light scattering does not provide good contrast. In this paper, spatial modulation spectroscopy (SMS) is used to image single organic nanoparticles doped with non-fluorescent, near-IR croconaine dye. SMS is a quantitative imaging technique that yields the absolute extinction cross-section of the nanoparticles, which can be used to determine the number of dye molecules per particle. SMS images were recorded for particles within EMT-6 breast cancer cells. The measurements allowed mapping of the nanoparticle location and the amount of dye in a single cell. The results demonstrate how SMS can facilitate efforts to optimize dye-doped nanoparticles for effective photothermal therapy of cancer.